Multirate filtering for digital signal processing : MATLAB applications Ljiljana Milic. - Milic´, Ljiljana, 1939- (Information Science Reference, 2009)
"This book covers basic and the advanced approaches in the design and implementation of multirate filtering"--Provided by publisher